FISHERIES AND ENVIRONMENTAL IMPACTS IN THE GREAT JAKARTA BAY ECOSYSTEM - Hari Eko Irianto; Sri Turni Hartati; Lilis Sadiyah (Indonesian Fisheries Research Journal, 2017)
The Great Jakarta Bay Ecosystem (GJBE) supports the economic growth for the surrounding community, including fisheries sector. This large ecosystem is consisted of two coastal ecosystems, i.e. Jakarta Bay and Thousands islands. There are only traditional fisheries operating either in Jakarta Bay or Thousand islands. Some economically important fisheries include shrimp, demersal and small pelagic fisheries, which are caught using different fishing gears, either active or passive fishing gears. There are some serious concerns related to the fish resources and habitat degradations in the GJBE, which in turn can cause the decrease in fish population and fish species diversity, respectively. CPUE and catch composition of the fixed lift nets, sero and fixed gillnet fisheries were obtained from the observations in 2006 and 2014. In addition, to determine the level of pollution, tissue samples were collected for green mussel (Perna viridis), blue swimming crab (Portunus pelagicus) and white-spotted spinefoot (Siganus canaliculatus) in 2009. The CPUE trend and catch composition showed that overfishing might have been occurring in the Jakarta Bay. The histological study on gill tissues of the three species shows that the Jakarta Bay has been polluted. Several efforts have been done to address the problems, including sea farming, habitat rehabilitation (artificial reef and mangrove restoration), marine conservation area and fish shelter, restocking and sea ranching.